Self-reported health following percutaneous coronary intervention: results from a cohort followed for 3 years with multiple measurements - Biering K (Clinical Epidemiology, 2014)
Karin Biering,1,2 Morten Frydenberg,3 Niels Henrik Hjollund4,5 1Department of Occupational Medicine, Regional Hospital West Jutland, Herning, Denmark; 2Danish Ramazzini Centre, Regional Hospital West Jutland, Herning, Denmark; 3Section of Biostatistics, Department of Public Health, Aarhus University, Aarhus, Denmark; 4WestChronic, Regional Hospital West Jutland, Herning, Denmark; 5Department of Clinical Epidemiology, Aarhus University Hospital, Aarhus, Denmark Objective: Improvements in the treatment of coronary heart disease have increased the number of patients living with a chronic heart disease. Patient-reported outcomes are required to adequately describe prognosis. We report self-rated health in a population-based cohort of patients with coronary heart disease treated with percutaneous coronary intervention (PCI). Methods: Over 3 years, we followed 1,726 patients under 65 years treated with PCI with eight repetitive questionnaires. With the use of multiple imputation, we described the course of self-rated health using the short form 12-item survey’s mental component summary (MCS) and physical component summary (PCS) and analyzed adjusted differences by sex, age, educational level, indication for PCI, and left ventricular ejection fraction along with an analysis of decrease in health status. Results: MCS scores increased during follow-up, while PCS scores were stable over time. Men rated higher in MCS and PCS than women, and older patients rated higher in MCS than younger. Other differences were negligible. Younger age was identified as a risk factor for marked decrease in mental health over time. Conclusion: In a complete population-based cohort of PCI patients with multiple measurements, we found improvements in mental, but not physical health over time. Demographic differences in health were larger than disease-related differences. Keywords: coronary heart disease, patient reported outcomes, multiple imputation, longitudinal study